Cinco monitos : leen en la cama - Christelow, Eileen ([New York] : Scholastic Inc., 2007)
After Mama reads them a bedtime story, the five little monkeys continue reading. When Mama hears them laugh at a funny book or scream at a scary book, she reminds them that it is time to sleep.
Cover title.
Text in Spanish.
Keywords: Reading -- Juvenile fiction; Bedtime -- Juvenile fiction; Monkeys -- Juvenile fiction; Five Little Monkeys (Fictitious characters) -- Juvenile fiction